Innovation and Development of English Language Learning Media Based on Information Technology at State Islamic College of Madina, North Sumatra - Dina Syarifah NST; M. Zaim; Haris Efendi Tahar (RETORIKA: Jurnal Ilmu Bahasa, 2024)
Recognizing the critical intersection of technology and education, particularly in language acquisition, the State Islamic College of Madina in North Sumatra undertook a study to investigate the innovation and development of English language learning media through Information Technology (IT) integration. The study aimed to address the following objectives: firstly, to identify the existing technological landscape in English language instruction; secondly, to assess the effectiveness of IT-based learning resources; and finally, to explore opportunities for improvement and future development in this domain. This research seeks to bridge the gap in literature by examining the nuanced impact of IT integration on English language education within the context of a religious institution. Employing a mixed-methods approach, data were gathered from students, educators, and administrators to gain insights into their perceptions of IT-based learning resources. The key findings revealed varying levels of technological competence among participants, impacting their engagement with IT tools. Educators emphasized the necessity of seamlessly integrating technology into lessons to enhance student engagement and learning experiences. Meanwhile, students acknowledged the convenience of digital resources but highlighted challenges such as technical issues and content relevance. Notable trends include the importance of investing in educator professional development and improving IT resource accessibility.